2003
DOI: 10.1074/jbc.m303737200
|View full text |Cite
|
Sign up to set email alerts
|

Aggrecan Protects Cartilage Collagen from Proteolytic Cleavage

Abstract: The matrix components responsible for cartilage mechanical properties, type II collagen and aggrecan, are degraded in osteoarthritis through proteolytic cleavage by matrix metalloproteinases (MMPs) and aggrecanases, respectively. We now show that aggrecan may serve to protect cartilage collagen from degradation. Although collagen in freeze-thawed cartilage depleted of aggrecan was completely degraded following incubation with MMP-1, collagen in cartilage with intact aggrecan was not. Using interleukin-1-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
218
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(229 citation statements)
references
References 34 publications
9
218
0
2
Order By: Relevance
“…Interestingly, the aggrecanase-selective inhibitor delayed and reduced hydroxyproline release to the media and loss from the explant by 50%. These results are consistent with a previously proposed model in which aggrecan protects the collagen network from proteolytic attack in bovine nasal cartilage (Pratta, et al, 2003b).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, the aggrecanase-selective inhibitor delayed and reduced hydroxyproline release to the media and loss from the explant by 50%. These results are consistent with a previously proposed model in which aggrecan protects the collagen network from proteolytic attack in bovine nasal cartilage (Pratta, et al, 2003b).…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, the aggrecanase-selective inhibitor also conferred some protection of the collagen network. Using a different small-molecule aggrecanase inhibitor, Pratta et al observed a similar result and hypothesized that aggrecan molecules can prevent MMPs from reaching their substrates on collagen fibers, perhaps by steric exclusion (Pratta, et al, 2003b). Treatment of IL-1-stimulated cartilage with the aggrecanase-selective inhibitor reduced cumulative collagen release by 50% through day 24 of the experiment, and delayed but did not prevent aggrecan release over the same period.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The reversible nature of aggrecan loss from the tissue suggests that the key pathological activity is the degradation of type II collagen. However, recent studies have suggested that aggrecan protects the collagen network from proteolysis and have demonstrated that prevention of aggrecan cleavage diminishes both aggrecan loss and cartilage erosion in arthritic model systems (Little et al, 2007;Pratta et al, 2003). Aggrecan proteolysis may therefore be a critical initiating step in these pathologies.…”
Section: Cartilage: Chondrocyte Apoptosis and Extracellular Matrix Dementioning
confidence: 99%